Clinical case of mechanical and non-mechanical rhabdomyolysis complicated by acute kidney injury. Case report - Evgeniy N. Ievlev; Daria R. Bekhtereva; Zukhra R. Khuzina; Edgar K. Chalgubaev; Irina N. Chekmareva (ZAO "Consilium Medicum", 2024)
To date, the problem of rhabdomyolysis remains relevant in Russia. Despite the introduction of modern methods of diagnosis, prevention and treatment, mortality remains high, up to 40%, especially with the addition of acute kidney injury. This article presents a clinical case of rhabdomyolysis, which arose as a result of the combined effects of non-traumatic (toxic effects of methadone, alcohol) and traumatic (vibration and non-physiological position during sleep) factors. This syndrome eventually led to the development of acute kidney damage up to anuria. In this clinical case, intensive infusion and detoxification therapy, including hemodialysis procedures, was carried out, which led to an almost complete restoration of the functional state of the kidneys. Thus, early diagnosis of rhabdomyolysis and AKI based on anamnesis, timely laboratory and instrumental diagnosis can prevent severe kidney damage up to terminal uremia and fatal consequences.